Application of graphene in energy storage device – A review - Olabi, A.G.; Abdelkareem, Mohammad Ali; Wilberforce, Tabbi; Sayed, Enas Taha (Renewable & sustainable energy reviews, 2021)
Most applications in energy storage devices revolve around the application of graphene. Graphene is capable of enhancing the performance, functionality as well as durability of many applications, but the commercialization of graphene still requires more research activity being conducted. This investigation explored the application of graphene in energy storage device, absorbers and electrochemical sensors. To expand the utilization of graphene, its present limitations must critically be addressed to improve their current performance. Again, in terms of applications, the advantages of graphene has widened their application in both electroanalytical and electrochemical sensors. These good characteristics of graphene must be extended further and improved to make them suitable for other applications. Critical study of facile synthesis of graphene coupled with detailed investigation into the structure of graphene oxide at the molecular level will equally improve the performance of this novel material. Effects of defects on the performance of graphene oxide was also identified as another key area of research that needs much attention to accelerate the commercialization of this material. With the rapid growth in the application of the graphene in different energy storage/conversion applications, it is essential to summarize and discuss the up-to-date progress in the application of graphene in these fields.